2022
DOI: 10.1007/s10055-021-00619-x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of consumer VR-headsets’ objective and subjective field of view (FoV) and its feasibility for visual field testing

Abstract: Virtual reality as a research environment has seen a boost in its popularity during the last decades. Not only the usage fields for this technology have broadened, but also a research niche has appeared as the hardware improved and became more affordable. Experiments in vision research are constructed upon the basis of accurately displaying stimuli with a specific position and size. For classical screen setups, viewing distance and pixel position on the screen define the perceived position for subjects in a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“… 5 for optokinetic nystagmus-based CS examinations. Although there are some considerable technical limitations, as for instance the eye-tracking latency 43 or its quality, 44 the VR headsets provide a bigger field of view for possible testing of larger eccentricities, 45 compared to our setup. Testing further eccentricities would be useful in the early detection of several eye diseases such as glaucoma.…”
Section: Discussionmentioning
confidence: 99%
“… 5 for optokinetic nystagmus-based CS examinations. Although there are some considerable technical limitations, as for instance the eye-tracking latency 43 or its quality, 44 the VR headsets provide a bigger field of view for possible testing of larger eccentricities, 45 compared to our setup. Testing further eccentricities would be useful in the early detection of several eye diseases such as glaucoma.…”
Section: Discussionmentioning
confidence: 99%
“…This headset has a display resolution of 1440 1600 pixels per eye, 90 Hz refresh rate and a FOV of 110° as stated by the manufacturer. Recent work by Sauer et al ( 47 ) found the official FOV specifications for most VR headsets to be overstated and reports the effective FOV of the Vive Pro Eye at 94° horizontally. The HMD is equipped with an eye tracking system running at 120 Hz sampling rate and reported to achieve a spatial accuracy of 0.5° - 1.1° ( 25 ).…”
Section: Methodsmentioning
confidence: 99%
“…The headset has an integrated eye tracker with a sampling frequency of 120 Hz and a known latency between 58 ms and 80 ms [ 38 , 39 ]. The HMD has two AMOLED screens, each with a resolution of 1.440 × 1.600 pixels, meaning a pixel density of 615 pixels per inch (PPI) for each eye, a field of view of 94 × 91 (horizontally per vertically) [ 40 ], a luminance of 116.1 cd m −2 [ 40 ] and a refresh rate of 90 Hz. The Tobii Pro SDK v1.7.1.1081 [ 41 ] was used to save the eye-tracking data.…”
Section: Materials and Methodsmentioning
confidence: 99%